In vitro exposure to 2, 2′, 4, 4′-tetrabromodiphenyl ether (PBDE-47) impairs innate inflammatory response. (March 2019) - Longo, Valeria; Longo, Alessandra; Di Sano, Caterina; Cigna, Diego; Cibella, Fabio; Di Felice, Gabriella; Colombo, Paolo
Abstract: Polybrominated diphenyl ethers (PBDEs) are persistent organic pollutants that are added to numerous products to prevent accidental fires. PBDEs are present in the environment and they bio-accumulate in human and animal tissues. Recently, their presence has been correlated to several pathologies but little is known about their effect on the human innate immune system activity. In this study we investigated the effect of the congener 2, 2′, 4, 4′-Tetrabromodiphenyl ether (PBDE-47) on the functional activity of the THP-1 human macrophages cell line and on ex vivo freshly isolated human basophils. Cytotoxicity and genotoxicity studies showed that PBDE-47 was able to induce toxic effects on the THP-1 cell line viability at concentrations ≥25 μM. Immune function of THP-1 was studied after stimulation with bacterial lipopolysaccharide (LPS) and PBDE-47 exposure at concentrations granting macrophage viability. Two dimensional electrophoresis showed modification of the proteome in the 3 μM PBDE-47 treated sample and Real Time PCR and ELISA demonstrated a statistically significant reduction in the expression of IL-1β, IL-6 and TNF-α cytokines. Furthermore, PBDE-47 was able to perturbate genes involved in cell motility upregulating CDH-1 and downregulating MMP-12 expressions. Finally, basophil activation assay showed reduced CD63 activation in PBDE-47 treated samples. In conclusion, our study demonstrated that PBDE-47 may perturb the activities of cells involved in innate immunity dampening the expression of macrophage pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) and genes involved in cell motility (MMP-12 and E-cadherin) and interfering with basophil activation suggesting that this compound can impair innate immune response. Highlights: PBDEs are POPs accumulating in human and animal tissues. PBDEs presence has been correlated to several pathologies. PBDE-47 exposure has been evaluated in vitro in the LPS differentiated THP-1. PBDE-47 impairs basophil activation in ex vivo freshly isolated human PBMC. PBDE-47 exposure can impair innate immune response.